Due to covid-19 perform the survey study about plant height (soybean & chickpea) at different temperature range (maximum/minimum) - Ruhi Khan (Open Journal of Plant Science - Peertechz Publications, 2020)
Our article is briefly define my self , it is based on the plant life . In which i describe that how plant response under normal temperature. The changes in the temperature over the next 30-50 years are predicted to be in the range of 2-3°C . Our script are not based on the academic experimental method . In this work i was used seeds of soybean & chickpea only for to know  how plant responses under normal temperature condition with normal tap water. I was put the some seeds of soybean & chickpea, and was sowing different pots with fertile soil. This work is related to our dissertation experiment, and i was apply at in my indoor garden due to crisis (Covid-19) period. I have identify that the impact of maximum and minimum temperature range on height of  both plant only at  one month time period. Result of this work, at normal temperature with enough water supply the height of both plant normal but at the high temperature the plant height decline. Extreme temperature events may have short term duration of a few days with temperature increase of over 5°C above the normal temperature. This script suggested that kept the poted plant  under normal temperature range with required water.